2021
DOI: 10.1016/j.ajogmf.2020.100275
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial mitochondrial oxidative stress in response to preeclampsia: a role for angiotension II type 1 autoantibodies

Abstract: BACKGROUND: Preeclampsia is characterized by a new onset of hypertension during pregnancy and is associated with autoantibodies against the angiotensin II type 1 receptor and oxidative stress. There is growing evidence for mitochondrial dysfunction in preeclampsia, however, the culprits for mitochondrial dysfunction are still being defined. We previously demonstrated that angiotensin II type 1 autoantibodies cause renal, placental, and endothelial mitochondrial dysfunction in pregnant rats. However, the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…Notably, we demonstrated that the blockade of circulating AT1-AA from human PE sera was able to attenuate mtROS in HUVECS cultured with PE sera with and without AT1-AA blockade [23]. In addition to the AT1-AA, our lab has recently investigated the importance of mt oxidative stress in PE pathology, and has linked reduced vascular endothelial mt respiration and mtROS with the presence of CD4+ T cells stimulated in response to placental ischemia [23][24][25][26][27][28][29]. In a previous study from our groups, we showed that LD recombinant IL-2 improved T regs cell in RUPP rats.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Notably, we demonstrated that the blockade of circulating AT1-AA from human PE sera was able to attenuate mtROS in HUVECS cultured with PE sera with and without AT1-AA blockade [23]. In addition to the AT1-AA, our lab has recently investigated the importance of mt oxidative stress in PE pathology, and has linked reduced vascular endothelial mt respiration and mtROS with the presence of CD4+ T cells stimulated in response to placental ischemia [23][24][25][26][27][28][29]. In a previous study from our groups, we showed that LD recombinant IL-2 improved T regs cell in RUPP rats.…”
Section: Discussionmentioning
confidence: 84%
“…Previously, McCarthy [28] showed vascular mtROS and decreased respiration in HUVECs exposed to sera from PE patients compared to HUVECS cultured with sera from normal pregnant women, thus indicating the importance of the release of soluble factors in the circulation to cause cellular mt dysfunction. Notably, we demonstrated that the blockade of circulating AT1-AA from human PE sera was able to attenuate mtROS in HUVECS cultured with PE sera with and without AT1-AA blockade [23]. In addition to the AT1-AA, our lab has recently investigated the importance of mt oxidative stress in PE pathology, and has linked reduced vascular endothelial mt respiration and mtROS with the presence of CD4+ T cells stimulated in response to placental ischemia [23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Notably, the elevated uterine vascular resistance is decreased by 'n7AAc', a capped inhibitory peptide binding to the AT 1 -AA and blocking AT 1 -AAs from binding to the AT 1 receptor [310]. Prolonged incubation of HUVECs with serum from preeclamptic patients suppresses mitochondrial respiration and increases mitochondrial ROS [311]. The increased mitochondrial ROS following exposure to serum from preeclamptic patients is reduced by 'n7AAC' [311].…”
Section: Autoimmunitymentioning
confidence: 99%